Deskripsi Surga dalam Syair Ibnu Qayyim Al-Jawziyyah dan Nāzik Al-Malā’ikah; Kajian Sastra Banding - Saidah, Siti Roudhotus; Wardani, R. Yaniah; Rokhim, Minatur; Pratama, M. Haikal Habibi; Auliyah, Nurul (Study Program of Arabic Language Teaching, 2025)
This study compares two Arabic poems from different historical periods, namely Waṣf al-Jannah by Ibn Qayyim al-Jawziyyah and Ādam wa Firdawsuhu by Nāzik al-Malā’ikah, to examine how each poet constructs the imagery and meaning of paradise within distinct aesthetic systems. The research employs a qualitative literary approach based on Wellek and Warren’s intrinsic and extrinsic framework, complemented by Tötösy de Zepetnek’s systemic approach. The data consist of poetic texts that represent images, symbols, and thematic expressions of paradise in both poems. The primary data are drawn from recognized editions of Waṣf al-Jannah, contained in Hādī al-Arwāḥ ilā Bilād al-Afrāḥ, and Ādam wa Firdawsuhu, included in Nāzik al-Malā’ikah al-Mujalladu al-Awwal. The secondary data are obtained from relevant scholarly studies in Arabic literary criticism. Data were collected through close reading and textual documentation focusing on diction, imagery, symbolism, and emotional tone related to the representation of paradise. Data analysis was conducted by examining intrinsic elements such as theme, imagery, diction, and symbolism, as well as extrinsic aspects including socio-historical context and literary conventions, which were then interpreted using a systemic perspective. The findings suggest that Ibn Qayyim portrays paradise through vivid sensory imagery inspired by Qur’anic descriptions, employing metaphors of light, gardens, flowing rivers, and eternal rewards to evoke spiritual longing and reinforce religious motivation. In contrast, Nāzik portrays paradise as an inner and psychological realm marked by loss and existential tension, using symbolic language to reflect modern concerns such as violence, alienation, and human fragility. The study concludes that representations of paradise are shaped not only by theological perspectives but also by cultural and aesthetic environments, demonstrating how poetic discourse bridges classical and modern Arabic literary traditions.